Introduction to clinical psychology [CD] - Compas, Bruce (México : McGraw-Hill, 2002)
This CD-ROM contain Macromedia Shockware, Player and macromedia flash, player software
El CD requiere de la instalación de aplicaciones
El CD está todo en inglés
Keywords: PSICOLOGIA CLÍNICA -- AUDIOVISUAL; PSICOTERAPIA -- AUDIOVISUAL; PERSONALIDAD -- AUDIOVISUAL; FISIOLOGÍA -- AUDIOVISUAL; CLINICAL PSYCHOLOGY -- AUDIOVISUAL